2019
DOI: 10.21873/anticanres.13237
|View full text |Cite
|
Sign up to set email alerts
|

ROBO1 Expression in Metastasizing Breast and Ovarian Cancer: SLIT2-induced Chemotaxis Requires Heparan Sulfates (Heparin)

Abstract: Background: The members of the slit homolog (SLIT) and roundabout homolog (ROBO) families have emerged as important signaling molecules in tumor metastasis. This study analyzed their role in regulating breast cancer (BC) cell motility and chemotaxis and assessed expression of ROBO1 in brain metastases (BMs) of breast, lung, and colon cancer, and in peritoneal metastases (PMs) of ovarian cancer. Materials and Methods: The BC cell line MDA-MB231 was subjected to scratch, motility, and chemotaxis assays using hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Among the identified TYW2 targets, we selected the roundabout guidance receptor 1 (ROBO1) for further validation and study. ROBO1 was selected because it is reportedly lost in some colorectal tumors ( 30 , 31 ) and because of its proposed role as an inhibitor of cell migration and epithelial-to-mesenchymal transition (EMT) ( 32 , 33 ). We first validated the RNA expression levels observed in the RNA-seq approach by quantitative real-time RT-PCR, and found that the TYW2 unmethylated/expressing HCT-116 and SW480 cells expressed the ROBO1 transcript, whereas CRISPR/Cas9-mediated inactivation of TYW2 induced the loss of ROBO1 transcript levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified TYW2 targets, we selected the roundabout guidance receptor 1 (ROBO1) for further validation and study. ROBO1 was selected because it is reportedly lost in some colorectal tumors ( 30 , 31 ) and because of its proposed role as an inhibitor of cell migration and epithelial-to-mesenchymal transition (EMT) ( 32 , 33 ). We first validated the RNA expression levels observed in the RNA-seq approach by quantitative real-time RT-PCR, and found that the TYW2 unmethylated/expressing HCT-116 and SW480 cells expressed the ROBO1 transcript, whereas CRISPR/Cas9-mediated inactivation of TYW2 induced the loss of ROBO1 transcript levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that the Slit2-Robo1 signaling pathway participates in the growth, migration and distribution of axons of neurons in the central nervous system and malignant cancer cells. [15][16][17] However, details on the expression of Slit2 and Robo1 in the intestines of patients with HD have rarely been reported. Therefore, this study focused on the axon guidance factor Slit2 and assessed the expression and distribution of Slit2 and its receptor Robo1 in diseased segments (spastic and transitional segments) and normal segments of the intestinal tract from children with HD.…”
Section: Observational Studymentioning
confidence: 99%
“…HD is a form of intestinal malformation caused by local ganglion cell loss due to inhibition of the differentiation of neurons migrating into the intestines into ganglion cells. Numerous studies have shown that the Slit2–Robo1 signaling pathway participates in the growth, migration and distribution of axons of neurons in the central nervous system and malignant cancer cells [15–17] . However, details on the expression of Slit2 and Robo1 in the intestines of patients with HD have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Slit2/ROBO1 signaling is reported to exert antitumor activity (5,6). This antitumor effect is attributed to the regulation of b-catenin and chemotaxis (7). Recent studies also highlight the dual nature of Slit2 in cancer suppression or progression based on whether the tumor or surrounding cells produce and secrete this protein.…”
Section: Introductionmentioning
confidence: 99%